KAJIAN HUKUM TENTANG PERLINDUNGAN KORBAN BULLYING: Legal Study On Protection Of Bullying Victims - Gede Tusan Ardika; Ramli Ramli; Aline Febriany Loilewen; Titin Titawati (Yayasan Al-Amin Qalbu, 2025)
Bullying cases are increasingly rampant, resulting in death or murder. The purpose of this study is to examine the law on the protection of bullying victims. The research method used in this writing is the normative legal research method and literature. The results of the study show that Indonesia is one of the countries that regulates protection for bullying victims and sanctions for perpetrators of bullying. Law Number 23 of 2002 concerning Child Protection (Child Protection Law),